Prevalence of Sigmoid Sinus Dehiscence and Diverticulum among Adults with Skull Base Cephaloceles - Sotoudeh, H. (AJNR Am J Neuroradiol, 2020)
BACKGROUND AND PURPOSE: Cephaloceles are relatively rare conditions caused by a congenital and/or acquired skull defect. The incidence of associated venous brain anomalies with regard to cephaloceles remains to be fully elucidated. Accordingly, we sought to assess the prevalence of sigmoid sinus dehiscence and diverticula in patients with spontaneous skull base cephaloceles. MATERIALS AND METHODS: Our institutional data base was retrospectively queried from 2005 to 2018. Patients in whom spontaneous skull base cephaloceles were identified were ultimately included in the study cohort. These patients subsequently had their sigmoid sinuses re-evaluated with focused attention on the possible presence of dehiscence and/or diverticula. RESULTS: We identified 56 patients: 12 men and 44 women. After re-evaluation of the sigmoid sinuses, evidence of dehiscence and/or diverticula was noted in 21 patients. The right sigmoid sinus was involved in 11 patients, and the left sigmoid sinus was involved in 7 patients, including 3 cases of diverticulum. In 3 patients, evidence of bilateral sigmoid sinus dehiscence and diverticula was noted. Female sex was associated with sigmoid sinus dehiscence and diverticula by univariate analysis (P = .019). By linear regression, cephalocele volume was negatively associated with sigmoid sinus dehiscence and diverticula (coefficient, −2266, P value < .007, adjusted R(2) = 0.1077). By univariate logistic regression using average cephalocele volume as a cutoff, we demonstrate a statistically significant finding of lower volumes being associated with sigmoid sinus dehiscence and diverticula with an odds ratio of 3.58 (P = .05). CONCLUSIONS: The prevalence of sigmoid sinus dehiscence and diverticula in patients with cephalocele is high. Female sex is associated with sigmoid sinus dehiscence and diverticula. The cephalocele volume appears to be inversely proportional to sigmoid sinus dehiscence and diverticula.